2021
DOI: 10.1088/1742-6596/1827/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Web application vulnerability detection method based on machine learning

Abstract: In order to solve the security problems caused by network vulnerabilities, a web application vulnerability detection method based on machine learning is proposed to effectively prevent cross site scripting attacks of web applications and reduce the occurrence of network security incidents. Through the in-depth study of the existing security vulnerability detection technology, combined with the development process of machine learning security vulnerability detection technology, the requirements of security vuln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Lilan hu et al [24] presented an in-depth study of the existing security vulnerability detection technology, combined with the development process of machine learning security vulnerability detection technology, the requirements of the security vulnerability detection model are analyzed in detail, and a cross-site scripting security vulnerability detection model for web application is designed and implemented. Based on the existing network vulnerability detection technology and tools, the verification code identification function is added, which solves the problem that the data can be submitted to the server only by inputting the verification code.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lilan hu et al [24] presented an in-depth study of the existing security vulnerability detection technology, combined with the development process of machine learning security vulnerability detection technology, the requirements of the security vulnerability detection model are analyzed in detail, and a cross-site scripting security vulnerability detection model for web application is designed and implemented. Based on the existing network vulnerability detection technology and tools, the verification code identification function is added, which solves the problem that the data can be submitted to the server only by inputting the verification code.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, in this experiment, it was found that the SVM-based model had higher detection accuracy for malicious crawlers and extracting effective features could improve the detection accuracy. In 2021, Hu et al [13] designed and implemented an XSS attack detection model for web applications. This model added the verification code recognition function to solve the problem of submitting data to the server just by entering the verification code; this model had a low false positive rate.…”
Section: Related Workmentioning
confidence: 99%
“…In fact, most of the vulnerabilities currently existing in ECS belong to the XXS (Cross Site Scripting) injection vulnerability, which is often injected by attackers through related attack scripts and hidden in the cloud server. Once the relevant users visit the server, the vulnerability will immediately control the user and obtain the user's private information [8][9][10][11]. In addition, many cloud servers use HTML (Hyper Text Markup Language) language to complete running development, which requires low access to embedded scripts, and is prone to XSS vulnerabilities, causing serious security losses.…”
Section: Introductionmentioning
confidence: 99%